Aeration ponds for improved wastewater management at Universiti Teknologi MARA Johor Branch, Segamat Campus: a quality assessment / Narita Noh ... [et al.] - Noh, Narita; Ab Rahim, Noor Raifana; Asfar, Juwita; Mohd Darwis, Nur Zaidani Wati; Salamin, Maznah (Universiti Teknologi MARA, Sabah, 2025)
UiTM Johor decided to upgrade its wastewater treatment plant from an oxidation pond to an aeration pond due to the increasing population and availability of sufficient funding. This study was conducted to evaluate the effectiveness of the aeration pond over a 12-month period and compare the results with those from previous 12 months of using the oxidation pond. The data was obtained from a contractor appointed by UiTM to operate the wastewater treatment plant. The study conducted at UiTM Segamat Campus collected data on several water quality parameters, including pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Oil and Grease, Ammonia Nitrogen, Nitrate Nitrogen, and Phosphorus. The results showed that the effectiveness of the aeration pond was comparable to that of the oxidation pond. However, several parameters, such as pH, COD, BOD, nitrate nitrogen, ammonia nitrogen, and TSS, were higher in the aeration pond compared to the oxidation pond. Despite this, all parameters studied complied with the Department of Environment (DOE) standards for both systems. Hence, further studies to improve the existing aeration pond to ensure long-term benefits for UiTM Johor in terms of energy consumption, maintenance, sludge management, and return on investment (ROI).